VULTURES BEFORE THE CONSTITUTIONAL COURT: THE CHEQUE IS IN THE MAIL Khohliso v S [2014] ZACC 33 - Eugene van der Berg; Avinash Govindjee (Obiter, 2016)
The legislative protection of wildlife in the Eastern Cape is not in what one would describe as a state of orderliness. Considering merely provincial or other regional legislation, one finds that there are at least three (four, if one includes the Problem Animal Control Ordinance 26 of 1957) such pieces of legislation operating simultaneously, or in parallel, depending upon where one finds oneself in the Eastern Cape, regulating the same subject matter. In the first place there is Decree 9 of 1992 which applies to what was once the independent homeland of Transkei before Transkei once again became part of the “new” South Africa, following the constitutional developments since 1993. Decree 9 was issued by presidential decree upon the recommendation of a Military Council, following a military coup which soon replaced the “democratic” government of the Transkei. Similarly there is the Nature Conservation Act 10 of 1987 (Ciskei) which applies to what was the independent homeland of Ciskei, which also became part of South Africa following the same constitutional developments since 1993. (The Ciskei too suffered a military coup soon after attaining independence.) As for the remainder of the Eastern Cape, the subject matter is regulated by the (Cape) Nature and Environmental Conservation Ordinance 19 of 1974, a creation of the Cape Provincial Council then in existence. The Provincial Councils were ultimately abolished by the Provincial Government Act 69 of 1986, and their law-making powers were transferred to the Executive.The result of this farrago of legislation is that the status of each piece is unclear. Do they constitute original legislation or delegated legislation, or did they constitute legislative acts as opposed to executive acts? As if the matter is not complicated enough, Parliament has adopted (national) legislation which overlaps with the subject matter regulated by the aforementioned provincial or regional legislation, namely the National Environmental Management: Biodiversity Act 10 of 2004 in terms of which the relevant Minister adopted the Threatened or Protected Species Regulations (GNR150 / GG29657 / 20070223). A new draft set of such Regulations has been published for comment (GN255 and 256 / GG38600 / 20150331).In 1994 the sovereignty of Parliament gave way to the rule of law and the supremacy of the Constitution of the Republic of South Africa, 1996 (the Constitution). The validity of legislation could now be challenged before the courts on the grounds that it was in conflict with the Constitution. In this regard section 167(5) of the Constitution provides that the Constitutional Court had to confirm an order of invalidity made by a High Court in respect of an Act of Parliament, a provincial Act or conduct of the President. In terms of section 172(2)(a), the declaration of invalidity had no force unless confirmed by the Constitutional Court.On 20 February 2010 Ms Nokhanjo Khohliso (“the Appellant”) ran afoul of the Transkei Decree 9 of 1992, having had in her possession two vulture feet in contravention of the Decree. The Appellant was a traditional healer and intended to use the feet as ingredients to a remedy designed to protect her clients against theft. For her troubles, the magistrate’s court handed her a sentence of a fine of R4000.00, or twelve months imprisonment. The Appellant appealed to the Eastern Cape High Court, Mthatha, against her conviction, essentially challenging the constitutionality of the provisions of the Decree in terms whereof she was convicted. The key question that is examined in this note is whether a declaration of such unconstitutionality is subject to confirmation by the Constitutional Court in terms of section 167(5) and 172(2)(a) of the Constitution (see above). Reduced to its essence, the issue is whether legislation of the nature of Decree 9 is subject to the abovementioned two sections.